IMPLEMENTASI KEBIJAKAN PENANGANAN COVID-19 : SUATU ANALISIS PENANGANAN COVID-19 DI DESA SAMPIRAN KECAMATAN TALUN KABUPATEN CIREBON - Althea Tahaanii Sutriana; Nur Rahman; Sarip Sarip; Feny Auliyah (Jurnal De Jure Muhammadiyah Cirebon, 2021)
The aim of study to find out and analyze the implementation of Covid-19 policies as stated in the West Java Governor Regulation Number 60 of 2020 concerning the Imposition of Administrative Sanctions for Violations of Health Order in the Implementation of Large-Scale Social Restrictions and New Life Adaptations in Coping With Covid-19. Analysis of the policy is considered very important considering that at this time there are still many people who have not implemented health protocols as happened in Sampiran Village, Talun District, Cirebon Regency. in Sampiran village, there are still many people who have not implemented health protocols as regulated in the West Java Governor Regulation, the factor regarding the lack of maximum community compliance is due to none other than the public's knowledge of the policy is still very minimal, so various socialization and education are needed from various parties, especially from the government, in addition, other efforts that can be made are so that policies regarding the prevention of Covid-19 can also be issued from several levels, such as Regency / City Regulations to Village Regulations in each region so that the level of public knowledge increases, which This will affect public understanding in controlling the spread of Covid-19. Keywords: Covid-19, rules, implementation.